What regional agricultural actors want to know about carbon dioxide removal in Northern Germany - El Zohbi, Juliane; Griesing, Lea; Torma, Gabriele; Rechid, Diana (Frontiers in Climate, 2025)
Many countries, including Germany, have made their climate targets dependent on the implementation of methods for removing carbon dioxide from the atmosphere. Actors in the agricultural sector can contribute to this implementation. However, there is a knowledge gap regarding carbon dioxide removal (CDR) among agricultural actors. In this study, we interviewed 34 agricultural actors at the micro, meso, and macro levels to identify the factors hindering the implementation of CDR practices, namely soil carbon sequestration, biochar, and agroforestry. We identified 22 information needs related to the dimensions of Climate change mitigation, Technological conditions, Environmental impacts, Economics, Policy & government, and Social aspects from the interviews. Farmers expressed more information needs compared with representatives from farming associations or local and regional administrations. Across all interviews, recommendations for action were most requested, with a high preference for information in digital online formats. Our findings provide a checklist for future research in the form of co-developed actionable knowledge between researchers and agricultural actors to increase the knowledge but especially the use of agricultural practices to remove carbon dioxide from the atmosphere.